Clinico-pathological Profile of Childhood Nonhodgkin Lymphoma (NHL) in A Tertiary Care Hospital in Bangladesh - Nahar, Kamrun; Hasan, Ahmed Rashidul; Islam, Afiqul; Jamal, Chowdhury Yakub (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Non-Hodgkin Lymphoma (NHL) is the third most common childhood malignancy. With histopathology based intensive chemotherapy and CNS-directed therapy, survival can reach more than 80%. Objective: The study was conducted to observe the clinico-pathological findings of NHL in Bangladeshi children. Methods: A prospective observational study was conducted in the Paediatric Haematology and Oncology Department of BSMMU from June 2012 to December 2012. Newly diagnosed NHL patients were included in the study. Patient’s initial clinical presentations, time interval from onset of symptoms to diagnosis were recorded. Diagnostic and staging workups were done by CBC, biochemistry, radio-imaging, histopathology (FNAC/excision biopsy), serous fluids/CSF cytology (cytospin), and bone marrow aspiration. Result: Among the 34 patients, BL had preponderance (n=23, 68%) then LL. Median age was 7.6 years. Male: female ratio was 2.1:1. Delayed diagnosis was found in 59% patient. Primary sites were abdomen (65%), thorax (32%), and head-neck (3%). At initial presentation, 83% patients of Burkitt NHL and 100% Lymphoblastic NHL patients came with advanced disease. Bone marrow involvement was found in 23.6% patients and 12% had CNS involvement at their presentation. Irrespective to histology, most common stage was stage-III, which was 53% and then stage-IV was 35%. Median LDH was 1719 U/L. Patient with abdominal variety of NHL came with abdominal complaint like pain (66%), distension (65%), ascites (48%), mass like hepatomegaly (39%), splenomegaly (26%), intussusceptions (8%), testicular involvement (4%). B symptoms were commonly found in 74% patient. Pallor (82%), anorexia, nausea & vomiting (48%), oedema (25%), peripheral lymphadenopathy (49%) were also noticed. In case of thoracic variety of NHL, most common presentation was respiratory distress (90%), superior mediastinal syndrome (SMS) (45%), with high incidence of B symptoms (90%), peripheral lymphadenopathy (72%) with other respiratory finding like chest bulging, mediastinal mass, pleural effusion was also found. Conclusions: About 59% childhood NHL patients tend to present with delayed diagnosis and 88% with advanced disease. Burkitt NHL is the commonest childhood lymphoma, mostly presented with abdominal complaint. Thoracic variety is mostly Lymphoblastic lymphoma. Histopathological findings following excisional biopsy is the most significant and confirmatory for diagnosis. Serum LDH were found significantly high level in both varieties. DS (Child) H J 2021; 37(1): 21-27